Geometric Duality in Multiple Objective Linear Programming - Heyde, Frank; Löhne, Andreas (SIAM journal on optimization, 2008)
We develop in this article a geometric approach to duality in multiple objective linear programming. This approach is based on a very old idea, the duality of polytopes, which can be traced back to the old Greeks. We show that there is an inclusion-reversing one-to-one map between the minimal faces of the image of the primal objective and the maximal faces of the image of the dual objective map.